The pathway of strengthening the working readiness: A study on graduate students of Islamic Economics and Business Faculty of UIN Walisongo Semarang - Zuhdan Ady Fataron; Rauly Sijabat (Jurnal Pendidikan Vokasi, 2019)
Research on working readiness is not a new thing. Nevertheless, studies related to working readiness still become interesting topic considering the empirical phenomena that indicate low working readiness. In addition, the results of previous studies have not provided conclusive conclusions about the factors that explain working readiness. This study was conducted to test the working readiness model developed in this study empirically by using the variable approach of training, apprenticeship, self-efficacy, and locus of control. Data on training, apprenticeship, self-efficacy, locus of control, and working readiness were obtained through interviews using a questionnaire conducted to the final semester students of the Islamic Economics and Business Faculty of UIN Walisongo Semarang. The research model testing was done by using SEM as an approach to the analysis technique. The test results show that training and apprenticeship are proven capable of explaining self-efficacy and locus of control. The results of this study also show that training, apprenticeship, self-efficacy, and locus of control are appropriate variables to explain variations in working readiness.